(untitled) (Economic and Political Thought, 2016)
The Holy See uses two kinds of diplomacy in international relations – classical (similar to that used by each state) and so-called ‘track two’ diplomacy (specific for non-state actors). In both cases the most important ‘interest’ of Catholic Church remains ensuring its followers the freedom of practice of religion, which at the same time serves to disseminate the religious freedom all over the world. Reconciliation is a part of the Vatican strategy of the ‘purification of memory’ that was proposed to the international community by John Paul II. But only by keeping its own basic principles, which are truth, justice, forgiveness and reconciliation, the strategy can give real and sustainable peace in the world.